A comparative clinicopathological study between ultrasonography, mammography, fine needle aspiration cytology and core needle biopsy of breast lump - Mandal, Arnab; Jana, Pradipta; Bakshi, Sabyasachi; Mandal, Ram Krishna (International Surgery Journal, 2020)
Background: Early presentation and prompt diagnosis is the essential key in treatment of different variety of neoplastic as well as non-neoplastic breast disease. In this study usefulness of high-resolution ultrasonography (HRUSG), mammography, fine needle aspiration cytology (FNAC) and core needle biopsy in correlation with histopathological pattern, was assessed. Methods: After matching the criteria, 212 cases, were taken for this prospective, single center, observational study. Results: Out of 212 cases, 163 (76.88%) were benign lesions, 49 (23.11%) were malignant and 1 (0.47%) were of inflammatory pathology. Benign to malignant breast disease ratio was 3.3:1. Out of 49 malignant cases, 45 (91.83%) were ductal cell carcinoma and 4 (8.16%) was apocrine carcinoma. Maximum numbers of cancer patients were found in the 51-60-year age groups. The sensitivity, specificity, positive predictive value and negative predictive value of mammography in detecting carcinoma breast were 87.76%, 64.71%, 87.76% and 64.71% respectively. The sensitivity, specificity, positive predictive value and negative predictive value of HRUSG in detecting carcinoma breast were 85.71%, 90.18%, 72.41% and 95.45% respectively. Among benign lesions, 47 (28.83%) were diagnosed by mammography and 147 (90.18%) were diagnosed by HRUSG. When these modalities were combined, >95% of the lesions was diagnosed accurately. Conclusions: Ultra sound used liberally as an adjunct to mammography, increase the cancer detection rate. Core needle biopsy is found more accurate but FNAC have limited value in evaluation of benign breast lump. This study also proves that preoperative categorization of breast lesions is utmost important for management of the patient and this will help to avoid unnecessary surgical treatment.